Analyzing Learning Boredom Dynamics in Mathematics and Science Lessons: A Case Study of Elementary School Students at SD Negeri 2 Bajur - Nurkhaerat Alimuddin; Aisa Nikmah Rahmatih; Ni Made Yeni Suranti (Indonesian Journal of STEM Education, 2024)
This research aims to determine the factors of learning boredom among students at SD Negeri 2 Bajur, Labuapi District, West Lombok Regency, Academic Year 2023/2024. This research uses descriptive qualitative research by conducting observations and case studies with data collection techniques using observation, interviews, filling out questionnaires and documentation. Qualitative data focuses on events that occur in the original environment. The results of the research conducted show that learning boredom experienced by students is at the medium category level and is largely influenced by monotonous learning methods, the learning environment, the last hour of learning, and the lack of variety of activities such as quizzes or games are the main triggers for boredom.